Implementasi Prosedur Pembiayaan Gadai Emas Pada Bank Syariah Indonesia KCP Medan Setia Budi - Gunawan, Dandi; Atika, Atika (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Indonesian Islamic bank KCP Medan Setia Budi is one of the banks that offers various types of finacing in order to increase income and improve products. One of which is a gold pawn product, in which a pawn product at the KCP medan setia budi Sharia bank, provides finacing Â facilities with collateral in the form of gold. this study aims to find out how the implementation of gold pawn finacing procedures at the Indonesian KCP medan setia budi.by using a filed approach, with direcct observation and interview methods, documentation and literature study. It can be concluded that the finacing procedures at Islamic banks in conducting gold pawn finacing arein accordance with the priciples of Islamic law and in accordance with the fatwa of the national sharia council of the Indonesia Ulema council number twenty six about rahn and also refers to the fatwa of the national sharia council of the indonesia ulema council number twenty five concerning rahn.